2008
DOI: 10.1897/08-098.1
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation and maternal transfer of polychlorinated biphenyls in snapping turtles of the upper Hudson River, New York, USA

Abstract: We conducted field studies over three years to assess body burdens and maternal transfer of polychlorinated biphenyls (PCBs) as well as indices of sexual dimorphism in snapping turtles (Chelydra serpentina) of the upper Hudson River (NY, USA.) We collected adult turtles in areas known to be contaminated with PCBs and in nearby reference areas for measurement of body size, precloacal length, and penis size. We analyzed PCB concentrations in eggs collected over three years and in whole blood from adults in one y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 34 publications
(102 reference statements)
1
26
0
1
Order By: Relevance
“…Maternal transfer of POPs to offspring is well documented in marine mammals (Aguilar & Borrell 1994, Debier et al 2003, Miranda-Filho et al 2007), birds (Fisk & Johnston 1998) and oviparous reptiles (Kelly et al 2008). In freshwater snapping turtles Chelydra serpentina, egg concentrations of PCBs, DDTs, mirex, octachlorostyrene and HCB were significantly correlated with concentrations in the blood, liver, muscle and adipose tissue of adult females (Hebert et al 1993, Pagano et al 1999, Kelly et al 2008.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Maternal transfer of POPs to offspring is well documented in marine mammals (Aguilar & Borrell 1994, Debier et al 2003, Miranda-Filho et al 2007), birds (Fisk & Johnston 1998) and oviparous reptiles (Kelly et al 2008). In freshwater snapping turtles Chelydra serpentina, egg concentrations of PCBs, DDTs, mirex, octachlorostyrene and HCB were significantly correlated with concentrations in the blood, liver, muscle and adipose tissue of adult females (Hebert et al 1993, Pagano et al 1999, Kelly et al 2008.…”
Section: Introductionmentioning
confidence: 98%
“…In freshwater snapping turtles Chelydra serpentina, egg concentrations of PCBs, DDTs, mirex, octachlorostyrene and HCB were significantly correlated with concentrations in the blood, liver, muscle and adipose tissue of adult females (Hebert et al 1993, Pagano et al 1999, Kelly et al 2008. Similarly, in leatherback sea turtles Dermochelys coriacea, significant correlations have been found between blood and egg samples containing DDTs, PCBs and PBDEs (Stewart et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our study focused on 2 species of aquatic turtles, snapping turtles and painted turtles Chrysemys picta, because these were the best represented elements of the reptile community in the upper Hudson River and are frequent targets of toxicological studies (Bergeron et al 1994, Bell et al 2006, including in the Hudson River (Hudson River Natural Resource Trustees 2005, Kelly et al 2008, Eisenreich et al 2009, Salice et al 2014. In addition to examining whether PCB exposure was associated with reduced turtle abundance, we assessed whether sex ratios were female-biased due to the feminizing effects of PCBs on developing embryos (Bergeron et al 1994), whether individual fitness was reduced as reflected in lower body condition, and whether physical deformities were more prevalent (Bell et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This chronic bioaccumulation can result in the maternal transfer of those compounds to their offspring during embryogenesis [12]. Several studies have documented maternal transfer of persistent contaminants to eggs in turtles as well as resultant effects on embryonic, hatchling, and juvenile health and development [13][14][15][16]. Kelly et al [15] demonstrated maternal transfer of polychlorinated biphenyls (PCBs) in snapping turtles collected from the upper Hudson River, NY, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have documented maternal transfer of persistent contaminants to eggs in turtles as well as resultant effects on embryonic, hatchling, and juvenile health and development [13][14][15][16]. Kelly et al [15] demonstrated maternal transfer of polychlorinated biphenyls (PCBs) in snapping turtles collected from the upper Hudson River, NY, USA. Hatchlings from eggs collected from the same area showed increased mortality beginning eight months after hatching, and mortality was correlated with total PCB concentrations in eggs [16].…”
Section: Introductionmentioning
confidence: 99%